(untitled) (AWKA JOURNAL OF ENGLISH LANGUAGE AND LITERARY STUDIES, 2023)
Contemporary African diaspora writing is characterized by issues of rejection, displacement, racism, and how these (re) constructs the character traits and personality of the African diaspora person as he oscillates between multiple countries and societies. This paper accounts for the construction of self and the behavioral traits and patterns of the characters represented in African diaspora writing. It argues that the psyche’s reaction to predominant social, political, psycho-social and economic realities is a major determinant of the neurotic turmoil or conflicts and personality traits that afflict characters in Taiye Selasi’s Ghana Must Go. This study adopts Karen Horney’s psychoanalytic principles in examining the intricacies of the human psyche or thought system which is central to psychoanalytic theory. Individuals’ social perceptions as regards to their place in society are pertinent in psychoanalysis. It is also key to defining self-determination and behavioral patterns. In contemporary analysis, psychoanalysis has been deployed to account for individual anxiety, depression, and other neurotic traits that determine personality development. Psychoanalysis does this, by beaming into the workings of the unconscious part of the human mind and how that is reflected in personal characteristics. This way, this study demonstrates among other things that there is a nexus between the individual characters’ behavioral traits in this novel and the prevailing cases of institutional racism and social turmoil in American society.